The apprenticeship system at the workshops - Oliver, Bobbie (University of Western Australia Press, 2006)
The chapter examines official and ‘unofficial’ aspects of the apprenticeship system at the Midland Government Railway Workshops. It discusses the length and aims of an apprenticeship, entrance requirements, the types of training experienced by the young men and the skills that they had to master before gaining their trade certificate, as well as the initiations, rituals, pranks, jokes and other experiences as revealed through personal anecdotes, interviews and memoirs. The chapter examines the ‘reputation’ of the Midland apprenticeship system for excellence and discuss the extent to which it was deserved; ways that changes to the system and the training over time altered the attitudes of the apprentices, and whether these changes were felt outside as well as inside the Workshops. It also considers the opportunities offered by a trade apprenticeship and the variety of occupations which Workshops-trained tradesmen entered if they left Midland at the conclusion of their apprenticeship. The chapter concludes that the Government Railway Workshops provided a through training that served many industries in the State and further afield. The Workshops’ closure in 1994 was a significant loss for apprenticeship training in Western Australia.